Design Model of Digital Dashboard Human Resources Information System based on Competence (Case Study at PT. Daya Adicipta Mustika) - Hamdani, Dani; Purno Wahyu, Arry; Sanihardjo, Rosalin (International Journal of Engineering and Technology, 2018)
CBHRM is one of the patterns of human resource management is being grown in Indonesia. In this approach, the vocabulary of competence to be a key element. Each employee will be assessed on its competence. In order results can be more optimally achieved, it would require a model of presentation of the good report/well output. One of the solutions the authors propose is to use a digital model of the dashboard. The model was built using the dashboard frame of mind which has been adapted to the life cycle model. Case studies conducted at PT. Daya Adicipta Mustika, and digital dashboards built CBHRM consist of Talent Dashboard, Dashboard Gap Competencies, and Comparison Dashboard interrelated with each other.
Keywords: CBHRM; Dashboard; Competence.